Aplikasi Tata Tertib Berdasarkan Poin untuk Pelanggaran Siswa pada Sekolah Menengah Atas - Pulla Pandika Widodo (UIN Sunan Kalijaga Yogyakarta, 2019)
Schools are A tool to gain formal education. Schools have rules that must be followed, these rules are called the Code of Conduct. This code of conduct is binding and has sanctions based on points for each violation. Each student is given a book that contains school rules that must be followed. If a violation is committed by a student, the teacher who processes it will mark the violation committed in the code of conduct book. This book is held by each student, of course this is very risky, if this book is lost it can be difficult for the teacher who will process other student violations if the student commits another violation. So because it is designed an application that can manage this order so that no longer need the code of conduct held by each student. Each violation will be input directly by the teacher who processes it into the application and the number of points will increase along with the number of violations committed by students